Optimizing Pancreas Transplantation Outcomes in Obese Recipients. Issue 6 (June 2015) - Laurence, Jerome M.; Marquez, Max A.; Bazerbachi, Fateh; Seal, John B.; Selzner, Markus; Norgate, Andrea; McGilvray, Ian D.; Schiff, Jeffrey; Cattral, Mark S.
Abstract : Background: Pancreas transplant recipient obesity has been associated with increased risk of perioperative complications, graft failure, and death. The imperative to maximize organ utility must be balanced against the need to maintain equity of access, including for the increasing number of obese diabetic patients. Methods: We compared the outcomes of pancreas transplant recipients with body mass index (BMI) greater than 30 kg/m 2 (n=60, mean±SD BMI 32.1±1.7 kg/m 2 ) to those with BMI less than 30 kg/m 2 (n=308, mean±SD BMI 24.5±2.7 kg/m 2 ) between 1996 and 2013. Results: There were no differences in the pretransplant recipient or donor characteristics apart from BMI. The BMI greater than 30 group were more likely to suffer a rejection episode (43% vs. 29%; P = 0.03). The median time to first rejection was shorter (1 vs. 6 months; P = 0.04), and wound infection was more common in the BMI greater than 30 group ( P = 0.03). There was no difference in the rate of patient, pancreas, or kidney graft survival or difference in graft function between the two groups. Conclusion: The obese recipients in this study were in the lower range of the obese category. Although there was an increased risk of rejection and wound infection in the obese group, there was no difference in patient or graft survival. This finding, when compared with previous reports, may be related to stringent recipient selection and posttransplant care particularly with respect to cardiovascular disease. Abstract : This large, single-center, retrospective analysis reports on pancreas allograft recipient outcomes with respect to body mass index (BMI). Recipients with higher BMI have increased incidences of rejection and wound infection, yet have equivalent patient and graft survival, suggesting that with careful selection criteria, obese recipients benefit from pancreas transplantation.